Analysis of thermal power plant fly ash and lime in increasing shear strength of soft clay. Issue 1 (April 2020) - Mohamed, S F W; Yahya, S
Abstract: Soil is the basic foundation for any civil engineering structures. It is required to bear the loads without failure. In some places, soils are weak which cannot resist the oncoming loads. Soft clay is known to have low strength and high compressibility. Utilization of additive is a method that can be applied to increase shear strength of soft clay. This study was conducted to determine the effectiveness of mixing fly ash, lime and soft clay with different percentage in order to increase the strength. A series of laboratory test were conducted in determining the physical properties, compaction and shear strength on soft clay soil. The soil samples; both disturbed and undisturbed were obtained from the vicinity of Politeknik Sultan Idris Shah (PSIS). Two tests carried out are compaction and direct shear strength. From the results, the highest strength of soft clay was at 69 kPa by mixing soil with 12% fly ash + 4% lime.